New Generating Functions Pertaining To Generalized Mellin-Barnes Type of Contour Integrals (Global Journal of Science Frontier Research, 2012)
The aim of the present paper is to evaluate new generating functions of H-function, using Truesdell's ascending and descending F-equation technique. These formulae are unified in nature and act as the key formulae from which we can obtain as their special cases. For the sake of illustration, we record here some special cases of our main formulae, which are believe to be new and important themselves.
Keywords: -function; generating function; F-equations